Induksi Ketahanan Tanaman Tomat terhadap Ralstonia syzygii subsp. indonesiensis Menggunakan Bakteri Endofit dan Asam Salisilat : Induction of Resistance in Tomato Plants Against Ralstonia syzygii subsp. indonesiensis Using Endophytic Bacteria and Salicylic Acid - Nababan, Triwanto; Lisnawita, Lisnawita; Safni, Irda (Jurnal Fitopatologi Indonesia, 2025)
Induction of Resistance in Tomato Plants Against Ralstonia syzygii subsp. indonesiensis Using Endophytic Bacteria and Salicylic AcidRalstonia syzygii subsp. indonesiensis causes bacterial wilt disease in tomato plants. This pathogen is difficult to control because the pathogen can persist in residual host material, and soil, and easily spread through water and infected plant tissue systemically. There are no chemical pesticides available to control bacterial wilt pathogens. Therefore, the alternative is biological control using endophytic bacteria and salicylic acid. Two endophytic bacteria, namely Arthrobacter sp. and Bacillus thuringiensis, as well as salicylic acid, were used in research singly or in combination to evaluate their potential in inducing tomato plant resistance in suppressing the bacterial wilt disease R. syzygii subsp. indonesiensis. The research uses a non-factorial completely randomized design with 14 single and combination treatments. Each treatment consisted of three experimental units and was repeated three times. The results showed the combination of Arthrobacter sp. and salicylic acid applied once a week (ABAS1) was the most effective treatment in inducing tomato resistance. Evidenced by the longest incubation period, low incidence and disease severity, increased peroxidase, polyphenol oxidase activity, and xylem tissue was not predominantly colonized by pathogens in histopathological observations.